76.1k views
5 votes
Now find the change in x. The change in x is . The average rate of change of f(x) = x2 + 5x −−12 from x = −2 to x = 1 is

2 Answers

3 votes

Answer:

The person above is correct but the change in x is -3

Explanation:

4 votes

Answer:

The average rate of change = 4.

Explanation:

Here we have formula.

Average rate of change = f(b) - f(a)

-----------

b - a

Given: f(X) = x^2 + 5x - 12 interval [-2, 1]

Here a = -2 and b = 1

f(a) = f(-2) = (-2)^2 + 5(-2) -12

= 4 -10 -12

f(-2) = -18

f(b) = f(1) = (1)^2 + 5(1) - 12

= 1 + 5 -12

f(1) = 6 -12

f(1) = -6

Now apply these values in the above formula, we get

Average rate of change = [-6 - (-18)] / [1 -(-2)]

= [ -6 +18]/1 +2

= 12/3

= 4.

Therefore, the average rate of change = 4.

Hope this will helpful.

Thank you.

User BarryWalsh
by
5.9k points